2012
DOI: 10.1002/zaac.201200227
|View full text |Cite
|
Sign up to set email alerts
|

Mixed Valence Tungsten (IV, V) Compounds with Layered Structures (Part IV): Syntheses, Crystal Structures, and Conductivity of BiX2[W2O2X6] (X = Cl, Br)

Abstract: The reaction of metallic bismuth with either tungsten tetrachlorideoxide WOCl 4 at 650 K or tungsten tetrabromideoxide WOBr 4 at 670 K, respectively, leads to BiX 2 [W 2 O 2 X 6 ] (X = Cl, Br) as black, lustrous crystal needles. The crystal structure determinations (triclinic, P1) show the two isotypic structures to be closely related to Hg 0.55 [W 2 O 2 Cl 6 ] with the presence of 1D-polymeric W 2 O 2 X 6 double strands. Dinuclear [Bi 2 X 4 ] 2+ cations are embedded in the host structure via secondary W-X···B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The 4 + 1 coordination environment for W and Mo is uncommon. Some selected Mo- and W-constituted oxybromides are summarized in Table S5. The four or six coordination environments for Mo and W atoms are the most common. Our study also confirmed that the distortion degree of 1D [WO 5 ] strands plays a critical role in determining NLO and PL properties (vide infra).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The 4 + 1 coordination environment for W and Mo is uncommon. Some selected Mo- and W-constituted oxybromides are summarized in Table S5. The four or six coordination environments for Mo and W atoms are the most common. Our study also confirmed that the distortion degree of 1D [WO 5 ] strands plays a critical role in determining NLO and PL properties (vide infra).…”
Section: Resultsmentioning
confidence: 99%
“…Oxybromides are compounds constructed by O 2– and Br – as anions. The chemically distinct O 2– (ionic size: 126 pm; electronegativity: 3.4) and Br – (ionic size: 182 pm; electronegativity: 3.0) made most oxybromides as ordered heteroanionic compounds, which results in pliable structural chemistry and fruitful physical phenomena, such as nonlinear optical properties. In this work, we report the crystal structure and growth, electronic structures, chemical bonding pictures, linear and NLO properties, and photoluminescent (PL) properties of LaBrMoO 4 and LaBrWO 4 . LaBrMoO 4 was structurally characterized without any property measurements.…”
Section: Introductionmentioning
confidence: 99%